A Fatal Case of Pediatric Primary Myxoid Liposarcoma of the Orbit: A Rare Tumor in an Unusual Location Presenting with Widespread Metastasis. (28th October 2020) - Baqir, A; Xie, Q
Abstract: Introduction/Objective: A liposarcoma is a tumor derived from primitive mesenchymal cells undergoing adipose differentiation. Liposarcomas are uncommon in childhood, representing only about 2% of childhood sarcomas. Among liposarcomas, is a very rare subtype, the so-called 'pleomorphic myxoid liposarcoma' which has extensive myxoid changes and scattered pleomorphic cells. Here we report an autopsy case of an extensively metastatic pleomorphic myxoid liposarcoma. Methods: A 12 year-old, African-American boy presented in the ED with ascites and shortness of breath, who later expired despite resuscitation. Autopsy finding showed a primary lesion in the left superior orbital fissure with diffuse metastasis to liver, replacing most of the liver parenchyma (liver weigh 8500 g). Metastatic foci are also present in gallbladder, pancreas, large intestine, bilateral lungs, and inner and outer surfaces of cranium. Histologically, tumor at all sites shows similar morphology, revealing scattered pleomorphic lipoblasts and a myxoid background with arborizing vasculature. Lipoblasts show indented and distorted nuclei and cytoplasmic vacuoles. Immunohistochemically the tumor cells are immunoreactive for p16 (diffusely and strongly) (Figure, D) and S100 (weakly) and negative for AE1/AE3, myogenin, synaptophysin, GFAP, EMA, and CD34. FISH was negative for MDM2 and t(12;16)(q13;p11.2) FUS-DDIT3 rearrangement, ruling out conventional myxoid liposarcoma. Conclusion: This case shows the aggressive nature of a poorly studied entity in an uncommon age group and emphasize the need to study childhood liposarcomas in more detail.